Desain Desain Framework Gamifikasi Untuk Pengobatan Tuberkulosis Paru Pada Pasien Anak - Ivan Rachmawan (Universitas Multi Data Palembang, 2026)
The risk of failure of anti-tuberculosis drug therapy (OAT) especially for children with TB is very high. This is because pediatric TB patients experience boredom with the obligation to take OAT every day without interruption in the long term (6-8 months). Factors inability of children to express symptoms of the disease they are suffering and side effects of OAT also cause pediatric TB patients to be disobedient and refuse to undergo OAT therapy. Integration of game elements into the therapeutic process is a solution proposed in this study or often called gamification. Gamification is the use of game elements in non-game contexts that are expected to increase motivation, user involvement and change behavior. This study aims to create a gamification design to improve treatment compliance in children with pulmonary TB.